Effect of H2 flow rate and stand-off distance on the formation of phases in plasma-sprayed Al2O3 coatings. (2nd November 2017) - Dhakar, B.; Chatterjee, S.; Sabiruddin, K.
Abstract : Plasma-sprayed Al2 O3 coatings contain both metastable and stable phases of Al2 O3 . The formation of these phases is influenced by various process parameters, such as stand-off distance (SOD), gas flow rates, nozzle diameter and is also dependent on the melting and solidification behaviour of feedstock particles, as these help in controlling the weight fraction of different phases formed in the coating. The present work reports the investigation on the effect of two major plasma spray parameters, namely secondary gas (H2 ) flow rate and SOD, on the formation of phases in plasma-sprayed Al2 O3 coating. The phases were identified by X-ray diffraction analysis and to quantify those phases, the Rietveld refinement method was used. The influence of α-phase on the mechanical properties of the Al2 O3 coatings was evaluated, and it has been observed that α-phase content decreases with the increase in secondary gas flow rate. With the increase in SOD, the α-Al2 O3 phase content first decreases and then increases.